Wear And Friction On Loaded Conveyor Belt - Iswady, Fateen Adibah (Universiti Sains Malaysia, 2018)
Wear and friction have been known as one of the major causes that affect the life time of conveyor belt system. It may become undesirable as it caused consequence of impact toward the system itself. There are various parameter that lead to this wear and friction problem. For instance service maintenance, surface morphology, material the belt convey and many more. For this research study, focused on investigation and make further research on wear behaviour of rubber compound (80% acrylonitrile butadiene rubber NBR and 20% natural rubber NR) by varying the influential parameter standard such as the effect of parameter of wear track diameter, sliding speed and also the load it’s convey had been study. Then also to identify the optimum combination of parameter use during the usage of conveyor belt in order to run the conveyor in appropriate standard and improve the life span of the system. For this purpose, a simple design of experiment using Pin on disc machine are being done to get the result for wear and friction of the belt material by using Taguchi method. The specimen was fabricate by using hot press machine and undergo several mechanical testing such as tensile test, tear test and hardness test. Profilometry are done to measure surface’s profile to quantify its roughness and waviness. On top of that,Scanning electron microscope (SEM) analysis is carried out to analyse the structure of the fractured surfaces. For the wear refer to volume loss, the optimum value to obtain the lowest amount is by using speed of 50 rpm, load of 10 N and wear track diameter of 50mm. Meanwhile, speed of 100 rpm with load of 50 N and 100 mm of wear track diameter were calculated to obtain the minimum number of coefficient of friction possible. By having optimum configuration of parameter setting, the wear and friction during the application of conveyor belt system could be reduced in order to prolong its life time.